The Appeal and Reception of the Legend of Saint Eustace in Early Medieval England and Medieval Scandinavia - McIntosh, James (University of Cambridge, 2020)
The Legend of Saint Eustace (BHL 2760) is an unusual saint’s life which was widely circulated in medieval Europe, but has received relatively little scholarly attention beyond its roots in folklore and the sources used in vernacular translations. This is especially the case for its reflexes that can be linked to tenth-century England and medieval Scandinavia. This thesis will examine the transmission and reception of the Legend in early medieval England, focusing on the tenth century, and in medieval Scandinavia, where the West Norse tradition in Norway and Iceland is active between the eleventh and nineteenth centuries. Several relevant reflexes of the tradition will undergo close textual analysis – the Latin base Legend (as extant in Cambridge, Corpus Christi College 9), an Old English translation, a putatively English Latin versification, a Norse skaldic versification and four Norse prose translations. A second, less popular Eustace tradition (represented by BHL 2761 and its versification) will also be examined to provide further context. This analysis will utilise a combination of polysystem theory and skopos theory to ascertain the intended audiences for the various reflexes and the intentions of the redactors in transmitting the Legend. In so doing, this thesis will examine the development of the Eustace tradition and its reception across chronological and geographic areas which, while in some ways distinct, are culturally linked. It will also explore the ways in which the Legend challenged the boundaries of sanctity and genre and interacted with other traditions, especially that of the study of Boethius, and how these aspects affected its reception and popularity in England and Scandinavia. The thesis will be accompanied by an edition and translation of the Latin base text as extant in CCCC 9 and an edition and translation of the potentially English Latin versification, which has no official translation and was last edited in 1881. These will provide valuable material for future researchers of the early ...